Penerapan Metode Economic Order Quantity (EOQ) pada Pengendalian PersediaanTiket Berhadiah di PT Trans Rekreasindo - Givan, Bryan; Darono, Hanafi Eko; Elyana, Instianti (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2022)
PT Trans Rekreasindo is a company engaged in providing children and family playgrounds. In attracting customers PT Trans Rekreasindo has attractive prizes, one of which is a ticket with prizes. This research was made to find out how to control the inventory of ticket prizes implemented by PT Trans Rekreasindo which will be compared with inventory control using the Economic Order Quantity method. The writing method used by the writer is observation, interview, and documentation with qualitative outline results. PT Trans Rekreasindo made ticket reservations in 2019 with 24,000,000 tickets, with a frequency of ordering 12 times a year, and the number of one-time tickets ordered as many as 2,000,000 tickets. PT Trans Rekreasindo is still experiencing a shortage of prize tickets. If it is applied with the calculation of the PT Trans Rekreasindo EOQ method, it only applies the number of economic orders, that is 2,000,000 in one message and the order frequency is 12 times in one year. However, the safety stock did not apply for 197,110 and the reorder point was 663,779. PT Trans Rekreasindo should apply the EOQ method in full, apply safety stock calculations and reorder points so that they do not experience shortage of tickets in the future.